e-ASPECTS correlates with and Is predictive of outcome after mechanical thrombectomy - Pfaff, Johannes; Herweh, Christian; Schieber, Simon; Schönenberger, Silvia; Bösel, Julian; Ringleb, Peter A.; Möhlenbruch, Markus Alfred; Bendszus, Martin; Nagel, Simon (American journal of neuroradiology, 2017)
BACKGROUND AND PURPOSE: The e-ASPECTS software is a tool for the automated use of ASPECTS. Our aim was to analyze whether baseline e-ASPECT scores correlate with outcome after mechanical thrombectomy. MATERIALS AND METHODS: Patients with ischemic strokes in the anterior circulation who were admitted between 2010 and 2015, diagnosed by CT, and received mechanical thrombectomy were included. The ASPECTS on baseline CT was scored by e-ASPECTS and 3 expert raters, and interclass correlation coefficients were calculated. The e-ASPECTS was correlated with functional outcome (modified Rankin Scale) at 3 months by using the Spearman rank correlation coefficient. Unfavorable outcome was defined as mRS 4 - 6 at 3 months, and a poor scan was defined as e-ASPECTS 0 -5. RESULTS: Two hundred twenty patients were included, and 147 (67%) were treated with bridging protocols. The median e-ASPECTS was 9 (interquartile range, 8 -10). Intraclass correlation coefficients between e-ASPECTS and raters were 0.72, 0.74, and 0.76 (all, P < .001). e-ASPECTS (Spearman rank correlation coefficient =−0.15, P = .027) correlated with mRS at 3 months. Patients with unfavorable outcome had lower e-ASPECTS (median, 8; interquartile range, 7-10 versus median, 9; interquartile range, 8 -10; P = .014). Sixteen patients (7.4%) had a poor scan, which was associated with unfavorable outcome (OR, 13.6; 95% CI, 1.8 -104). Independent predictors of unfavorable outcome were e-ASPECTS (OR, 0.79; 95% CI, 0.63- 0.99), blood sugar (OR, 1.01; 95% CI, 1.004 -1.02), atrial fibrillation (OR, 2.64; 95% CI, 1.22-5.69), premorbid mRS (OR, 1.77; 95% CI, 1.21-2.58), NIHSS (OR, 1.11; 95% CI, 1.04 -1.19), general anesthesia (OR, 0.24; 95% CI, 0.07- 0.84), failed recanalization (OR, 8.47; 95% CI, 3.5-20.2), and symptomatic intracerebral hemorrhage (OR, 25.8; 95% CI, 2.5-268). CONCLUSIONS: The e-ASPECTS correlated with mRS at 3 months and was predictive of unfavorable outcome after mechanical throm- bectomy, but further studies in patients with poor scan are needed.